2015
DOI: 10.1111/jtxs.12128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Quinoa Flour on Quality Characteristics of Cookie, Bread and Chinese Steamed Bread

Abstract: Quinoa has unique physicochemical and nutritional properties among diverse food grains. Quinoa flour (QF) was blended into wheat flour (WF) at weight ratios of 85/15, 70/30, 55/45, 40/60, 25/75 and 10/90 to formulate composite flour for the production of cookie, bread and Chinese steamed bread (CSB). Physicochemical properties of quinoa–wheat composite flour (QWCF) and quality characteristics of the bakery products were characterized. The feasibility of using QF in CSB making was explored for the first time. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 34 publications
5
53
1
2
Order By: Relevance
“…Focusing on microbial spoilage, Hager et al (2012) found the first mould growth in breads from 100 % WF and 100 % QF (packed in a plastic bag) appeared on days 4 and 3, respectively. Wang et al (2015) also found that adding QF to WF bread prolonged the mould-free shelf lives of both bread and Chinese steamed bread. The visual appearances of the representative slices of breads of 100 % WF and QF (45 %) and WF (55 %) mixture stored at room temperature under aerobic conditions are depicted in Fig 4 ( Wang et al 2015).…”
Section: Shelf Lifementioning
confidence: 92%
See 4 more Smart Citations
“…Focusing on microbial spoilage, Hager et al (2012) found the first mould growth in breads from 100 % WF and 100 % QF (packed in a plastic bag) appeared on days 4 and 3, respectively. Wang et al (2015) also found that adding QF to WF bread prolonged the mould-free shelf lives of both bread and Chinese steamed bread. The visual appearances of the representative slices of breads of 100 % WF and QF (45 %) and WF (55 %) mixture stored at room temperature under aerobic conditions are depicted in Fig 4 ( Wang et al 2015).…”
Section: Shelf Lifementioning
confidence: 92%
“…Wang et al (2015) also found that adding QF to WF bread prolonged the mould-free shelf lives of both bread and Chinese steamed bread. The visual appearances of the representative slices of breads of 100 % WF and QF (45 %) and WF (55 %) mixture stored at room temperature under aerobic conditions are depicted in Fig 4 ( Wang et al 2015). The prolonged microbiological shelf life of bread could be due to the lower water activity of QF-containing bread than that of WF bread (Rodriguez-Sandoval et al 2012), and the presence of antimicrobial phytochemicals such as phenolics in quinoa grains (Miranda et al 2014).…”
Section: Shelf Lifementioning
confidence: 92%
See 3 more Smart Citations